Disentangling the complex broad-band X-ray spectrum of IRAS 13197−1627 with NuSTAR, XMM–Newton and Suzaku. Issue 4 (12th October 2017) - Walton, D. J.; Brightman, M.; Risaliti, G.; Fabian, A. C.; Fürst, F.; Harrison, F. A.; Lohfink, A.; Matt, G.; Miniutti, G.; Parker, M. L.; Stern, D.
Abstract: We present results from a coordinated XMM–Newton + NuSTAR observation of the type 1.8 Seyfert galaxy IRAS 13197−1627. This is a highly complex source, with strong contributions from relativistic reflection from the inner accretion disc, neutral absorption and further reprocessing by more distant material, and ionized absorption from an outflow. We undertake a detailed spectral analysis combining the broad-band coverage provided by XMM–Newton + NuSTAR with a multi-epoch approach incorporating archival observations performed by XMM–Newton and Suzaku . Our focus is on characterizing the reflection from the inner accretion disc, which previous works have suggested may dominate the AGN emission, and constraining the black hole spin. Using lamppost disc reflection models, we find that the results for the inner disc are largely insensitive to assumptions regarding the geometry of the distant reprocessor and the precise form of the illuminating X-ray continuum. However, these results do depend on the treatment of the iron abundance of the distant absorber/reprocessor. The multi-epoch data favour a scenario in which the AGN is chemically homogeneous, and we find that a rapidly rotating black hole is preferred, with a * ≥ 0.7, but a slowly rotating black hole is not strongly excluded. In addition to the results for the inner disc, we also find that both the neutral and ionized absorbers vary from epoch to epoch, implying that both have some degree of inhomogeneity in their structure.